Ultimate strength analysis of highly damaged plates. (January 2016) - Saad-Eldeen, S.; Garbatov, Y.; Soares, C. Guedes
Abstract: This work deals with the ultimate compressive strength of highly damaged plating resulting from dropping objects, grounding or collision. Extensive static nonlinear finite element analyses are conducted, where several governing parameters are considered. The effect of dent depth as well as dent size is studied. Different dent shapes are considered in order to cover different possible damage scenarios. The toughness modulus is used to measure the capacity of the plate to withstand the applied load with permanent deformation. An expression to estimate the average reduction of ultimate strength of highly damaged steel plates, subjected to compressive loading as a function of the residual breadth ratio is also developed. Highlights: This work deals with the ultimate compressive strength assessment of highly damaged plating. Extensive static nonlinear finite element analyses are conducted. Different dent shapes are considered in order to cover different possible damage scenarios. The toughness modulus is used to measure the capacity of the plate to withstand the applied load. An expression to estimate the average reduction of ultimate strength of highly damaged steel plates is developed.